Effect of Moringa oleifera on inflammatory diseases: an umbrella review of 26 systematic reviews - da Silva Parente, Thiala Soares Josino; Sarandy, Mariáurea Matias; de Araújo, Edilane Rodrigues Dantas; Gonçalves, Reggiani Vilela; Zucolotto, Silvana Maria (Frontiers in Pharmacology, 2025)
ObjectivesTo summarize and critically assess the quality of evidence from Systematic reviews (SRs) and meta-analyses (MAs) that have evaluated the effectiveness of Moringa oleifera (MO) in treating inflammatory diseases and understand the main pathways activated during this exposure.MethodsA systematic search of the literature was conducted from inception until 04 November 2024, using Embase, Scopus, Web of Science, PubMed/Medline, and Cochrane Library databases. The eligibility criteria were (i) SRs on MO; (ii) SRs on MO related to inflammatory diseases; (iii) No language, year, and model limitation. Literature selection and data extraction were conducted by two independent reviewers. The quality of SRs was evaluated using the PRISMA checklist and AMSTAR-2 tool adapted.Results and DiscussionTwenty-six SRs were included, covering a total of 573 primary articles. MO leaves were the most used parts of the plant; decoction was the main extraction method; ingestion of encapsulated powder, in tablets or added with a meal were the main method of preparation; water and ethanol were the most used solvents; and flavonoids, phenolic acids and isothiocyanates were the main constituents involved in the activities of MO. Many SRs showed a promising efficacy of MO for diabetes mellitus, obesity, cancer, hypertension, dyslipidemia, among other conditions, but the quality of these SRs is questionable. Only 6 SRs indicated that they followed PRISMA (2020), and, nevertheless, they did not reach even 80% of compliance with the checklist in our evaluation. The SRs was classified, predominantly, as of low methodological quality (≤7/16) after applying AMSTAR-2. NF-kB and Nrf2 appear to be the pathways involved in the anti-inflammatory and antioxidant mechanisms of MO, respectively.ConclusionMO is promising herbal medicine for healthcare, beneficial for inflammatory diseases, however, considering the lower level of the quality of different studies, in which the majority displayed a lack of standardization in their protocol (dose and pharmaceutical form used, use of plant powder instead of the extract, type of extraction, identification and quantification of different phytochemical markers), more well-design studies are required to confirm the conclusion.Systematic Review RegistrationRegistration: https://www.crd.york.ac.uk/PROSPERO, identifier CRD42022367195.